2009
DOI: 10.1002/adfm.200801419
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formation of Bi‐Component Arrays Through H‐Bonding of Multivalent Molecular Modules

Abstract: Here, the formation of discrete supramolecular mono- and bi-component architectures from novel and multivalent molecular modules bearing complementary recognition moieties that are prone to undergo multiple H-bonds, such as 2,6-di(acetylamino)pyridine and uracil residues, is described. These nanostructured H-bonded arrays, including dimeric and pentameric species, are thoroughly characterized in solution by NMR, in the solid state by FT-IR, and at the solid-liquid interface by means of scanning tunneling micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…H-bonds formed in uracil-based molecules have played a major role not only in nucleic acid research [1,2,3,4], but recently also as the secondary forces holding together two-dimensional networks with long-range order [5,6,7]. Numerous studies on the role of H-bonding in uracil and uracil derivative molecules have been reported [5,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H-bonds formed in uracil-based molecules have played a major role not only in nucleic acid research [1,2,3,4], but recently also as the secondary forces holding together two-dimensional networks with long-range order [5,6,7]. Numerous studies on the role of H-bonding in uracil and uracil derivative molecules have been reported [5,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…H-bonds formed in uracil-based molecules have played a major role not only in nucleic acid research [1,2,3,4], but recently also as the secondary forces holding together two-dimensional networks with long-range order [5,6,7]. Numerous studies on the role of H-bonding in uracil and uracil derivative molecules have been reported [5,8,9,10,11,12,13,14,15]. The study of uracil derivatives is of special interest as these compounds are excellent models to demonstrate the key role of supramolecular chemistry both in biochemistry and materials science, such as the formation of two-dimensional porous networks on surfaces [5,10,13,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to build such devices, the development, understanding and mastering of fabrication methods for the controlled engineering of well-defined organic structures is fundamental to the research activities [16,17]. Thus, the precise control and understanding of molecule-substrate, and molecule-molecule interactions, as well as their structural properties are crucial parameters for both the construction of electronic [4,5,[13][14][15][18][19][20][21][22][23] or biomedical [24,25] devices and also, for fine-tuning their performances. Chemical modification of the organic molecules provides a promising tool for the adjustment of such properties.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The deposition of mixtures of precursor molecules has led to more sophisticated architectures, mainly built on weak intermolecular interactions [10][11][12][13][14] or weak interactions in combination with coordination bonding, that is, hierarchical motifs. [9] The deposition of mixtures of precursor molecules has led to more sophisticated architectures, mainly built on weak intermolecular interactions [10][11][12][13][14] or weak interactions in combination with coordination bonding, that is, hierarchical motifs.…”
mentioning
confidence: 99%
“…Extended monolayers of open, two-dimensional (2D) coordination networks with high organizational periodicity, controlled symmetries, and modular dimensionality have been achieved by using designed, self-instructed molecular building blocks. [9] The deposition of mixtures of precursor molecules has led to more sophisticated architectures, mainly built on weak intermolecular interactions [10][11][12][13][14] or weak interactions in combination with coordination bonding, that is, hierarchical motifs. [15,16] The cooperative assembly of instructed mixtures of molecular bricks enables a high degree of structural control and functionality, for example, the stability and ordering of primary structures can be increased, [15] or the dimensionality and geometry of supramolecular structures can be steered.…”
mentioning
confidence: 99%